Putting psychology in its place : critical historical perspectives - Richards, Graham , 1941- (Routledge, 2010)
This book introduces the debates in psychology in an accessible way, making it suitable for beginners as well as those with some knowledge. A range of issues are covered from psychology and women, to a more traditional subject such as behaviourism